Drug-loaded bionic scaffold based on in-situ emulsified and homogenized PLGA microspheres, preparation method and application
By adding hydroxyapatite and photoinitiator to the collagen solution, combined with PLGA and drug solution for in-situ emulsification and homogenization technology, a homogenized PLGA microsphere drug-loaded bionic scaffold was prepared, which solved the problem of uneven particle size distribution of PLGA microspheres and long preparation process in the prior art, and achieved efficient drug encapsulation and controllable release process.
Patent Information
- Application Number
- CN202411852169.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, when preparing PLGA microspheres, the particle size distribution is uneven, and the preparation process takes a long time, resulting in a low drug encapsulation rate and uncontrollable release process.
Using in-situ emulsification homogenization technology, a homogenized PLGA microsphere drug-loaded bionic scaffold was prepared by adding hydroxyapatite and photoinitiator to the collagen solution, combining PLGA and drug solution, and oscillating emulsification and photocuring.
The dimensional uniformity of PLGA microspheres is achieved, the encapsulation rate of the drug is improved, and the drug release process can be regulated, which is suitable for the repair and treatment of different types of bone defects.
Smart Images

Figure CN119633173A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, and in particular to a drug-loaded bionic stent based on in-situ emulsified homogenized PLGA microspheres, a preparation method and an application thereof. Background Art
[0002] Bone defects have always been a major problem faced by clinical orthopedics, with the characteristics of long treatment time and great difficulty in treatment. Drugs or bioactive ingredients are expected to accelerate the functional reconstruction of bone defects. The bioavailability at the bone defect site after systemic administration is low, and increased drug dosage may lead to liver damage and kidney disease. Collagen / hydroxyapatite scaffolds that mimic the composition of natural bone have excellent value in bone defect repair, and their mediated delivery systems have also been involved in the delivery of drugs or bioactive ingredients to achieve highly precise and localized interventional treatment plans.
[0003] Microspheres refer to spheres with a diameter range of 1 to 1000 μm, which are usually used to load drugs in the process of bone defect repair. Its particle size is adjustable and the application form is free. It can be used as a carrier to improve the solubility of the drug and perform local sustained release of the drug, thereby extending the half-life of the drug. PLGA is a copolymer of polylactic acid PLA and polyglycolic acid PGA. It is one of the most widely used synthetic polymers in the field of microsphere manufacturing, with adjustable degradation rate and safe degradation byproducts. The emulsification method is the most commonly used PLGA microsphere preparation process, but the microspheres prepared by this method have a wide size distribution, poor particle size uniformity, and a long preparation process, which ultimately causes the drug encapsulation and release process to be uncontrollable. For example, CN105232474A discloses a simple method for preparing PLGA microspheres with uniform particle size, by adding glass beads to assist emulsification during the emulsification process to obtain PLGA microspheres with uniform size. CN108113975A discloses a method for preparing PLGA microspheres based on a vortex oscillator, and PLGA microspheres with uniform particle size are prepared by a vortex oscillator and glass beads. Although these methods can obtain PLGA microspheres with uniform particle size by adding auxiliary emulsifiers, these emulsifiers must be removed in the subsequent process. They fail to improve the shortcomings of the traditional emulsification method, and require a long solvent volatilization process, resulting in drug loss in the aqueous phase, leading to too low encapsulation efficiency. In addition, this process leads to discontinuous preparation and loading of microspheres, which increases the complexity of the preparation process of PLGA microsphere functionalized drug-loaded stents. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a drug-loaded bionic stent based on in-situ emulsified homogenized PLGA microspheres, a preparation method and application thereof.
[0005] The technical solution adopted by the present invention is: a method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres, comprising the following steps:
[0006] Step 1: Add hydroxyapatite to the collagen solution, mix thoroughly, add a photoinitiator, and react thoroughly to obtain a mixed solution A;
[0007] Step 2: After dissolving the polylactic acid-polyglycolic acid copolymer PLGA, add the drug solution to be loaded, and mix thoroughly to obtain a mixed solution B;
[0008] Step 3: Add the mixed solution B as the oil phase into the aqueous mixed solution A obtained in step 1, shake and emulsify, and then photocure to obtain the drug-loaded bionic scaffold containing the homogenized PLGA microspheres.
[0009] Furthermore, the collagen in step 1 is a methacrylic anhydride-modified type I collagen derivative.
[0010] Furthermore, the mass ratio of collagen to hydroxyapatite in step 1 is 1-3:20-40.
[0011] Furthermore, in step 1, the particle size of the hydroxyapatite particles is 10 to 70 μm.
[0012] Furthermore, in step 2, the weight average molecular weight of PLGA is 0.5-5.3 thousand, and the monomer ratio of lactic acid to glycolic acid is 85:15-10:90.
[0013] Furthermore, in step 3, the volume ratio of the oil phase to the aqueous phase solution is 1:6 to 1:10.
[0014] Furthermore, in step 3, the emulsification time is 30 to 60 seconds, and the light curing time is 30 to 120 seconds.
[0015] A drug-loaded biomimetic scaffold based on in situ emulsified and homogenized PLGA microspheres.
[0016] An application of a drug-loaded bionic stent based on in-situ emulsified homogenized PLGA microspheres, wherein the drug-loaded bionic stent is used for in-situ loading of drugs.
[0017] Furthermore, the drug is a drug for repairing and treating bone defects.
[0018] The beneficial effects of the present invention are:
[0019] (1) The present invention obtains a homogenized PLGA microsphere functionalized drug-loaded bionic scaffold, obtains PLGA microspheres of uniform size, improves the drug encapsulation rate, and can regulate the drug release process;
[0020] (2) The drug-loaded stent obtained by the present invention integrates microsphere preparation, drug encapsulation and bionic stent construction;
[0021] (3) The drug-loaded stent obtained by the present invention is suitable for loading all types of drugs in the bone repair process and is suitable for repairing and treating different types of bone defects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the bionic scaffold obtained in Example 1 of the present invention.
[0023] Figure 2 The fluorescence images and particle size distribution ranges of the PLGA microspheres prepared in situ in the bionic scaffolds obtained in Examples 1 to 3 of the present invention, A is the fluorescence image, B is the statistical results of Example 1 and Comparative Example 2, C is the statistical results of Example 2 and Comparative Example 3, and D is the statistical results of Example 3 and Comparative Example 4.
[0024] Figure 3 The encapsulation rate and release process of the drug-loaded bionic stent obtained in Example 2 of the present invention and the drug in the comparative example, A is the release process of the drug in Example 2 and Comparative Examples 1, 3, and 5, and B is the encapsulation rate of the drug in Example 2 and Comparative Example 3 containing microspheres. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0026] A method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres comprises the following steps:
[0027] Step 1: Add hydroxyapatite to the collagen solution, mix thoroughly, add a photoinitiator, and react thoroughly to obtain a mixed solution A;
[0028] The collagen is a methacrylic anhydride-modified type I collagen derivative with rapid light-curing properties. The mass ratio of collagen to hydroxyapatite is 1-3:20-40. The particle size of the hydroxyapatite particles is 10-70 μm.
[0029] Step 2: After dissolving the polylactic acid-polyglycolic acid copolymer PLGA, add the drug solution to be loaded, and mix thoroughly to obtain a mixed solution B;
[0030] The weight average molecular weight of PLGA is 0.5 to 5.3 thousand, and the monomer ratio of lactic acid to glycolic acid is 85:15 to 10:90.
[0031] Step 3: Add the mixed solution B as the oil phase into the aqueous mixed solution A obtained in step 1, and after hydroxyapatite-assisted oscillation emulsification, photocuring is performed to obtain the desired homogenized PLGA microsphere-loaded biomimetic scaffold.
[0032] The volume ratio of the oil phase to the water phase solution is 1:6 to 1:10. The emulsification time is 30 to 60 seconds, and the light curing time is 30 to 120 seconds.
[0033] An application of a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres, the drug-loaded bionic scaffold is used for in-situ loading of drugs and for drug loading in various bone repair processes.
[0034] Example 1
[0035] A method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres comprises the following steps:
[0036] Step 1: Prepare a 1wt.% methacrylic anhydride modified type I collagen solution, adjust the pH to 7.4, add hydroxyapatite particles with a particle size of 10-25 μm, and the mass concentration of hydroxyapatite particles is 10wt.%. After thorough mixing, add a photoinitiator as the water phase in the subsequent emulsification process.
[0037] Step 2: After dissolving polylactic acid-polyglycolic acid copolymer PLGA with a weight average molecular weight of 24,000 to 38,000 and a monomer ratio of 50:50, simvastatin solution (dissolved in the solvent of PLGA) is added to the solution, and the mixed solution is regarded as the oil phase in the subsequent emulsification process.
[0038] Step 3: Add the oil phase in step 2 to the water phase in step 1 in a volume ratio of 1:6, and quickly emulsify in a vortex oscillator for 30 seconds. After emulsification, place it under ultraviolet light for 60 seconds to quickly solidify to form a hydrogel, which is freeze-dried to obtain a drug-loaded bionic scaffold loaded with simvastatin microspheres. The microspheres obtained after the scaffold is degraded by collagenase are named collagen / hydroxyapatite / PLGA microspheres. Figure 2 Medium B result.
[0039] Example 2
[0040] A method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres comprises the following steps:
[0041] Step 1: Prepare a 1.5wt.% methacrylic anhydride modified type I collagen solution, adjust the pH to 7.4, add hydroxyapatite particles with a particle size of 25-40μm, and the mass concentration of hydroxyapatite particles is 20wt.%. After thorough mixing, add a photoinitiator as the water phase in the subsequent emulsification process.
[0042] Step 2: After dissolving the polylactic acid-polyglycolic acid copolymer PLGA with a weight average molecular weight of 38,000 to 53,000 and a monomer ratio of 10:90, add gentamicin sulfate solution (dissolved in physiological saline) to the solution, and regard the mixed solution as the oil phase in the subsequent emulsification process.
[0043] Step 3: Add the oil phase in step 2 to the water phase in step 1 at a volume ratio of 1:8, and quickly emulsify in a vortex oscillator for 60 seconds. After emulsification, place it under ultraviolet light for rapid curing for 120 seconds to form a hydrogel, which is freeze-dried to obtain a drug-loaded bionic scaffold (collagen / hydroxyapatite / PLGA scaffold) of gentamicin sulfate microspheres. The microspheres obtained after using collagenase to degrade the scaffold are named collagen / hydroxyapatite / PLGA microspheres. Figure 2 Medium C result.
[0044] Example 3
[0045] A method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres comprises the following steps:
[0046] Step 1: Prepare a 0.5wt.% methacrylic anhydride modified type I collagen solution, adjust the pH to 7.4, add hydroxyapatite particles with a particle size of 40-70μm, and the mass concentration of hydroxyapatite particles is 15wt.%. After thorough mixing, add a photoinitiator as the water phase in the subsequent emulsification process.
[0047] Step 2: After dissolving the polylactic acid-polyglycolic acid copolymer PLGA with a weight average molecular weight of 0.5 to 15,000 and a monomer ratio of 85:15, add icariin solution (dissolved in DMSO) to the solution, and regard the mixed solution as the oil phase in the subsequent emulsification process.
[0048] Step 3: Add the oil phase in step 2 to the water phase in step 1 in a volume ratio of 1:10, and quickly emulsify in a vortex oscillator for 50 seconds. After emulsification, place it under ultraviolet light for 30 seconds to quickly solidify to form a hydrogel, which is freeze-dried to obtain a drug-loaded bionic scaffold of icariin microspheres. The microspheres obtained after using collagenase to degrade the scaffold are named collagen / hydroxyapatite / PLGA microspheres. Figure 2 Medium D result.
[0049] The following comparative example is provided to illustrate the effect of the present invention.
[0050] Comparative Example 1
[0051] A 1.5 wt. % methacrylic anhydride-modified type I collagen solution was used, the pH was adjusted to 7.4, and then a photoinitiator was added as the aqueous phase.
[0052] The gentamicin solution was directly added to the aqueous phase solution at a volume ratio of 1:8, and after rapid oscillation for 60 seconds in a vortex oscillator, it was placed under ultraviolet light for rapid curing for 120 seconds to form a hydrogel, which was freeze-dried to obtain a gentamicin-loaded drug-loaded scaffold (collagen scaffold).
[0053] Comparative Example 2
[0054] A 1 wt. % methacrylic anhydride-modified type I collagen solution was prepared, the pH was adjusted to 7.4, and a photoinitiator was added after thorough mixing as the aqueous phase.
[0055] After dissolving polylactic acid-polyglycolic acid copolymer PLGA with a weight average molecular weight of 24,000 to 38,000 and a monomer ratio of 50:50, simvastatin solution (dissolved in a solvent of PLGA) was added to the solution, and the mixed solution was regarded as the oil phase in the subsequent emulsification process.
[0056] The oil phase was added to the aqueous phase solution in a volume ratio of 1:6, and the mixture was rapidly emulsified in a vortex oscillator for 30 seconds. After emulsification, the mixture was rapidly cured under ultraviolet light for 60 seconds to form a hydrogel, which was then freeze-dried to obtain a drug-loaded biomimetic scaffold loaded with simvastatin microspheres. The microspheres obtained after the scaffold was degraded by collagenase were named collagen / PLGA microspheres. Figure 2 Medium B result.
[0057] Comparative Example 3
[0058] A 1.5 wt. % methacrylic anhydride-modified type I collagen solution was prepared, the pH was adjusted to 7.4, and a photoinitiator was added after thorough mixing as the aqueous phase.
[0059] After dissolving polylactic acid-polyglycolic acid copolymer PLGA with a weight average molecular weight of 38,000 to 53,000 and a monomer ratio of 10:90, gentamicin sulfate solution (dissolved in physiological saline) is added to the solution, and the mixed solution is regarded as the oil phase in the subsequent emulsification process.
[0060] The oil phase was added to the aqueous phase solution in a volume ratio of 1:8, and the oil phase was added to the aqueous phase solution, and the oil phase was quickly emulsified in a vortex oscillator for 60 seconds. After emulsification, it was placed under ultraviolet light for rapid curing for 120 seconds to form a hydrogel, which was freeze-dried to obtain a drug-loaded scaffold (collagen / PLGA scaffold) of gentamicin sulfate microspheres. The microspheres obtained after the scaffold was degraded by collagenase were named collagen / PLGA microspheres. Figure 2 Medium C result.
[0061] Comparative Example 4
[0062] A 0.5 wt. % methacrylic anhydride-modified type I collagen solution was prepared, the pH was adjusted to 7.4, and a photoinitiator was added after thorough mixing as the aqueous phase.
[0063] After dissolving polylactic acid-polyglycolic acid copolymer PLGA with a weight average molecular weight of 0.5 to 15,000 and a monomer ratio of 85:15, icariin solution (dissolved in DMSO) was added to the solution, and the mixed solution was regarded as the oil phase in the subsequent emulsification process.
[0064] The oil phase was added to the aqueous phase solution in a volume ratio of 1:10 and rapidly emulsified for 50 seconds in a vortex oscillator. After emulsification, the solution was rapidly cured for 30 seconds under ultraviolet light to form a hydrogel, which was freeze-dried to obtain a drug-loaded scaffold of icariin microspheres. The microspheres obtained after the scaffold was degraded by collagenase were named collagen / PLGA microspheres. Figure 2 Medium D result.
[0065] Comparative Example 5
[0066] A 1.5wt.% methacrylic anhydride modified type I collagen solution was prepared, and after adjusting the pH to 7.4, hydroxyapatite particles with a particle size of 25-40 μm were added thereto, and the mass concentration of the hydroxyapatite particles after addition was 20wt.%. After thorough mixing, a photoinitiator was added as the water phase in the subsequent emulsification process.
[0067] The gentamicin solution was directly added to the aqueous phase solution at a volume ratio of 1:8, and after rapid oscillation for 60 seconds in a vortex oscillator, it was placed under ultraviolet light for rapid curing for 120 seconds to form a hydrogel, which was freeze-dried to obtain a gentamicin-loaded scaffold (collagen / hydroxyapatite scaffold).
[0068] The drug-loaded stent obtained in Example 1 was subjected to gold spraying treatment, and the morphology of the stent and PLGA microspheres was observed using a scanning electron microscope. Figure 1 As shown in the figure, hydroxyapatite particles are evenly distributed in the collagen network, forming an organic / inorganic bionic structure that mimics natural bone. In addition, PLGA microspheres were successfully prepared and uniformly sized and distributed in the scaffold.
[0069] The collagen / hydroxyapatite / PLGA scaffolds encapsulating different types of drugs in Examples 1-3 were degraded using collagenase, and the PLGA microspheres (collagen / hydroxyapatite / PLGA microspheres) therein were collected. At the same time, the collagen / PLGA microsphere group was set as the control group, and the fluorescence of the microspheres was photographed to determine the size distribution of the microspheres. The particle size of the microspheres was statistically analyzed using image J statistical software, and the results are shown in FIG. Figure 2 As shown. Figure 2 It can be seen that the particle size distribution of the collagen / hydroxyapatite / PLGA microspheres obtained in Examples 1 to 3 is more concentrated and the size is more uniform.
[0070] The different stents obtained in Example 2 and Comparative Examples 1, 3, and 5 were tested for drug release, and the drug encapsulation rate of Example 2 and Comparative Example 3 containing microspheres was tested. First, the different stents were placed in a neutral Tris-HCl buffer, and the release of the drug was tested at different time points. The drug absorbance was measured by a UV spectrophotometer, and the drug content was calculated by a standard curve. For drug encapsulation of PLGA microsphere stents, after the stent was degraded by collagenase, the drug microspheres were collected, the drug was dissolved with dimethyl sulfoxide, the drug absorbance was measured by a UV spectrophotometer, and the drug content was calculated by a standard curve. The encapsulation efficiency of the drug is calculated by the formula: encapsulation efficiency = mass of the drug in the microspheres / total amount of the drug added. As shown in 3, with the introduction of hydroxyapatite and PLGA, hydroxyapatite assists PLGA in forming a more controlled drug release process in the collagen solution, which can maintain the concentration of the drug in a safe and effective range for a longer time. In addition, the drug encapsulation efficiency was measured in the group containing PLGA microspheres. The collagen / hydroxyapatite / PLGA microsphere scaffold had a higher drug encapsulation efficiency. Figure 3 shown.
[0071] It can be seen from the figure that when the drug is directly in the collagen scaffold or directly in the collagen / hydroxyapatite scaffold, there will be a burst release of the drug, and the sustained release of the loaded drug cannot be achieved. By introducing PLGA microspheres to encapsulate the drug, both collagen / PLGA and collagen / hydroxyapatite / PLGA can effectively achieve sustained release of the drug. More importantly, in the collagen / hydroxyapatite / PLGA group, due to the role of hydroxyapatite-assisted emulsification, the obtained microspheres are more uniform, and when more drugs are encapsulated, they still show a better sustained release effect than collagen / hydroxyapatite (uneven microspheres).
[0072] The drug-loaded stent obtained by the present invention is designed using components approved for clinical use. First, thanks to the characteristics of rapid formation of a gel network by photo-crosslinked collagen, the PLGA microspheres encapsulating the drug can be rapidly encapsulated in situ in the stent by emulsification polymerization, and in this process, hydroxyapatite assists the uniformity of the PLGA microspheres as an auxiliary emulsifier. Therefore, in the in situ emulsification process, uniform PLGA microspheres are rapidly formed in the stent to achieve controllable drug release.
[0073] The present invention utilizes the organic phase-collagen and the inorganic phase-hydroxyapatite for constructing the bone biomimetic scaffold to quickly prepare and encapsulate the drug-loaded PLGA microspheres while constructing the scaffold, thereby reducing the loss and complexity of the drug in the preparation process. The PLGA microspheres with uniform particle size distribution can be obtained through the in-situ emulsification process assisted by hydroxyapatite, and the release and encapsulation process of the drug can be effectively regulated to prolong the action time of the drug. Under the joint action of hydroxyapatite, collagen and PLGA, a more controlled drug release process is mediated. This preparation method can encapsulate drugs with various dissolution characteristics in the bone repair process, and is expected to be applicable to various types of bone repair processes.
Claims
1. A method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres, characterized in that: The following steps are involved: Step 1: Add hydroxyapatite to the collagen solution, mix thoroughly, add a photoinitiator, and react thoroughly to obtain a mixed solution A; Step 2: After dissolving the polylactic acid-polyglycolic acid copolymer PLGA, add the drug solution to be loaded, and mix thoroughly to obtain a mixed solution B; Step 3: Add the mixed solution B as the oil phase into the aqueous mixed solution A obtained in step 1, shake and emulsify, and then photocure to obtain the drug-loaded bionic scaffold containing the homogenized PLGA microspheres.
2. The method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 1, characterized in that: The collagen in step 1 is a methacrylic anhydride-modified type I collagen derivative.
3. The method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 1, characterized in that: The mass ratio of collagen to hydroxyapatite in step 1 is 1-3:20-40.
4. The method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 1, characterized in that: The particle size of the hydroxyapatite particles in step 1 is 10 to 70 μm.
5. The method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 1, characterized in that: In the step 2, the weight average molecular weight of PLGA is 0.5-5.3 thousand, and the monomer ratio of lactic acid to glycolic acid is 85:15-10:
90.
6. The method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 1, characterized in that: In step 3, the volume ratio of the oil phase to the aqueous phase solution is 1:6 to 1:
10.
7. The method for preparing a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 1, characterized in that: In the step 3, the emulsification time is 30 to 60 seconds, and the light curing time is 30 to 120 seconds.
8. A drug-loaded bionic scaffold based on in-situ emulsified and homogenized PLGA microspheres obtained by any one of the preparation methods described in claims 1 to 7.
9. The use of a drug-loaded bionic stent based on in-situ emulsified homogenized PLGA microspheres as claimed in claim 8, characterized in that: The drug-loaded bionic stent is used for in-situ loading of drugs.
10. The use of a drug-loaded bionic scaffold based on in-situ emulsified homogenized PLGA microspheres according to claim 9, characterized in that: The medicine is a medicine for repairing and treating bone defects.
Citation Information
Patent Citations
Simple method for preparing PLGA microspheres with uniform particle size
CN105232474A
PLGA microsphere preparation method based on vortex oscillator and application thereof
CN108113975A